Analytical characterization of volatiles present in the whole body odour of zebra finches - Alves Soares, Tatjana; Caspers, Barbara A.; Veit, Daniel; Loos, Helene (Analytical and Bioanalytical Chemistry, 2024)
In recent decades, the compositions of preen oil and feathers have been studied to achieve insights into the chemistry of avian odours, which play a significant role in birds’ social behaviour. Fewer studies are available regarding volatiles originating from other sources, such as faeces, eggs or a bird’s whole body. The aims of this study were (i) to identify odour-active and further volatile compounds in zebra finch whole body odour and (ii) to semi-quantify selected volatiles and use the information to evaluate two different adsorbents for their suitability for whole body odour sampling. Volatiles from the headspace above zebra finches were sampled using an open loop system equipped with either activated charcoal or Tenax® TA. Samples were analysed by olfactory-guided approaches as well as gas chromatography–mass spectrometry. Using activated charcoal as sorbent, 26 odour-active and 73 further volatile compounds were detected, whereas with Tenax® TA 27 odour-active and 81 further volatile compounds were detected. In total, 104 compounds were (tentatively) identified, of which 22 had not been identified previously in zebra finch odour and 12 had not been described in any birds. Hints towards a chemical sex signature became evident for qualitative but not for quantitative differences. With the exception of some compounds, notably carboxylic acids and alkanes, relative peak areas obtained with the two adsorbent types were comparable. The approach described herein is proposed for future studies aiming to determine volatiles emitted by birds when, for example, parent birds are approaching the nest. Graphical Abstract: (Figure presented.)
CRIS-Team Scopus Importer:2024-08-30
Keywords: Bird odour; Chemical profile; Chemical sex signature; Gas chromatography–olfactometry; Open loop system; Taeniopygia castanotis